Determination of quantum numbers for several excited charmed mesons observed in B−→D*+π−π− decays; Physical Review D; Vol. 101, iss. 3 - Aaij R. Roel; Beteta C. A. Carlos Abellan; Ackernley T.; Eydelman S. I. Semen Isaakovich; Kharisova A. E. Anastasiya Evgenjevna; Panshin G. L. Gennady Leonidovich (2020, 2020)
Title screen